1999
DOI: 10.1002/(sici)1098-2353(1999)12:5<382::aid-ca9>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic determinants in the etiology of class III malocclusions: A review

Abstract: Morphospatial disharmony of the craniomaxillary and mandibular complexes may yield apparent mandibular prognathism, but Class III malocclusions can exist with any number of aberrations of the craniofacial complex. Deficient orthocephalization of the cranial base allied with a smaller anterior cranial base component has been implicated in the etiology of Class III malocclusions. Whereas the more acute cranial base angle may affect the articulation of the condyles resulting in their forward displacement, the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 171 publications
(181 reference statements)
1
34
0
2
Order By: Relevance
“…With an obtuse angle all the procedures that reduce prominence of the chin should be avoided. The finding coincide with the result obtained by Jain and Kalra [16] in which they reported that lower faceethroat angle was more obtuse in males than females and also AL-Jasser (2003) [22] study of selected Saudi population suggested that, lower faceethroat angle in males greater than females 109.90 and 102.90 respectively. When the lip form was assessed, the upper lip as well as lower lip was found to be more protrusive in males than in females and hence, the nasolabial angle was more acute, but the difference in nasolabial angle was statistically insignificant.…”
Section: Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…With an obtuse angle all the procedures that reduce prominence of the chin should be avoided. The finding coincide with the result obtained by Jain and Kalra [16] in which they reported that lower faceethroat angle was more obtuse in males than females and also AL-Jasser (2003) [22] study of selected Saudi population suggested that, lower faceethroat angle in males greater than females 109.90 and 102.90 respectively. When the lip form was assessed, the upper lip as well as lower lip was found to be more protrusive in males than in females and hence, the nasolabial angle was more acute, but the difference in nasolabial angle was statistically insignificant.…”
Section: Variablessupporting
confidence: 89%
“…Sometimes the esthetic result is more important to the patient than the occlusal changes. Hence, good occlusion and improved facial appearance are distinct yet parallel objectives of orthodontic treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors are also convinced that vomero-palatine suture is important for anterior-inferior displacement of palatal bone. Traumatic nasomaxillary complex leads to abnormalities in the growth of nasal septum, and surrounding muscle dysfunction may affect the subsequent growth of the facial massif 7 . Accordingly, the growth of nasomaxillary complex is the result of two main mechanisms: passive transfer, which is due to the growth of cranial base, which "pushes" maxilla forward and active growth of maxillary and nasal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal class III malocclusion is a classic example of "easy to be recognized but difficult to treat", the situation where sometimes orthodontic possibilities are limited and need support from other specialties, particularly surgery [22][23][24] . However, the key to a successful treatment lies in understanding and integrating these two specialties in seeking the best alternatives and procedures, as it was in our case where the treatment was carried out through orthodontic preparation and orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%